CONSTRUCTION OF ELEMENTARY SCHOOL SAFETY CLIMATE: THE ROLE OF IDEALIZED INFLUENCE AND INSPIRATIONAL MOTIVATION OF THE PRINCIPAL - fathimah; Ngurah Ayu Nyoman Murniati; Supandi (SOSIOEDUKASI, 2026)
The escalation of child violence and post-disaster infrastructure damage in elementary schools demands a resilient leadership model. This study aims to analyze the implementation of the principal's Idealized Influence and Inspirational Motivation strategies in building trust and resilience within the school community. Using a qualitative case study method at SDN 2 Ketangirejo, data was collected through interviews, observations, and analysis of the 2023-2024 Education Report Card. The findings indicate that the leadership's moral example and inspirational vision successfully created a "psychological shield" that compensated for physical vulnerability, as evidenced by an increase in the security index from 68.02 to 75.99. However, administrative vulnerabilities were identified in the instructional leadership aspect. As a solution, a "Resilient-Systemic-Instructional" (RSI) model was formulated that integrates collective leadership, data-driven operational standardization, and strengthened academic supervision to ensure the sustainability of a comprehensive school safety climate.